Follow-up of women with inadequate Pap smears: a prospective cohort study - López-Alegría, Fanny; Lorenzi, Dino Roberto Soares De; Poblete, Orlando Quezada (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: Inadequate Pap smears do not provide satisfactory cell samples for evalua-tion, thus making it more difficult to detect cervical cytological abnormalities. The objective of this study was to determine the cytological and histological follow-up results from women with inadequate smear reports in primary healthcare centers in Santiago, Chile 2010-2011. DESIGN AND SETTING: Prospective cohort study at primary healthcare clinics in Santiago, Chile. METHODS: The population was taken from the “Cito-Expert” database of 2010. The data were then or-ganized according to the cytological and histological follow-up results of 2,547 women with inadequate cervical cytological reports over the 12-month period. The samples were assigned to groups based on the cause of inadequacy (smears with endocervical cells alone; insufficient, hemorrhagic, inflammatory or poorly fixed samples; insufficient and hemorrhagic samples; or insufficient and inflammatory specimens). The data were analyzed using the “conditional probability tree diagram” and descriptive statistics. RESULT: Half of the women (n = 1,285) met the requirements of the Ministry of Health for repeating these inadequate smears, and 1,104 of these women had normal cytological results (85.9%). The detection rate for cervical lesions according to group ranged from 0% (smears with endocervical cells alone or insuf-ficient and hemorrhagic specimens) to 4.1% (poor fixation). CONCLUSION: The large proportion of normal results justifies revision of the current clinical guidelines. The results showed that it is not necessary to repeat the Pap test early on, with the exception of inadequate hemorrhagic and inflammatory cytological results.